Soil Fungal Diversity and Community Structure of Russula griseocarnosa from Different Sites - Zhen Li; Ruoxi Liang; Fei Yu (Microorganisms)
Russula griseocarnosa is an important ectomycorrhizal edible fungus whose economic and nutritional value are both high. To better understand which abiotic and biotic factors affect the growth of R. griseocarnosa, this study examined the mycosphere soil of R. griseocarnosa growing in five sites. The soil fungal communities of R. griseocarnosa from five sites of Fujian, Guangxi, and Yunnan Provinces were sequenced by Illumina MiSeq technology, and their community structure comprehensively analyzed in combination with a suite of soil physicochemical properties. The results revealed significantly greater levels of available potassium (AK), available nitrogen (AN), and available phosphorus (AP) in mycosphere soil than bulk soil, and that R. griseocarnosa prefers acidic soil, with Penicillium, Trichoderma, Talaromyces, Mortierella, Tolypocladium, Chloridium, Oidiodendron, and Umbelopsis being the main dominant fungal taxa. Different geographical sites had different indicator fungal genera, and the similarity of fungal communities in the mycosphere decreased with increasing geographical distance among them. Soil pH was the major abiotic factor influencing the structure of the mycosphere fungal communities. Management strategies such as nitrogen, potassium, phosphorus mixed fertilizer, and fungal fertilizer can promote the conservation and sustainable utilization of R. griseocarnosa.